Mathematics and physics for programmers [ - Flynt, John P.; Kodicek, Danny (Course Technology, 2012)
Teaches beginning game programming students the skills they need to develop causal games. Beginning with the basic aspects of mathematics and physics that are relevant to games, and moving on to complex topics, this book combines theory and practice and helps the student to develop many games